2019
DOI: 10.1097/olq.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Sexually Transmitted Infection Screening Rates by Symptomatic Status Among Men Who Have Sex With Men in the United States: A Hierarchical Bayesian Analysis

Abstract: Self-reported rates of STI screening were close to CDC's recommended overall annual screening frequency, but with gaps defined by demographics and behavioral risk. Targeted screening efforts may be indicated specifically for younger MSM and those with multiple partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…This demonstrates the value of targeted screening compared with population-level screening, similar to findings surrounding the importance of focusing on a core group for prevention of disease transmission [30]. In the model, as infections decreased, fewer than 10% of testing events were symptoms-driven, consistent with empirical data from MSM [22]. It is important to note that previous analyses have shown that if there were an influx of new STI cases into the MSM population, potentially imported from other areas or from bridging with heterosexual populations, reduced screening levels could lead to a rebound in infections [15].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This demonstrates the value of targeted screening compared with population-level screening, similar to findings surrounding the importance of focusing on a core group for prevention of disease transmission [30]. In the model, as infections decreased, fewer than 10% of testing events were symptoms-driven, consistent with empirical data from MSM [22]. It is important to note that previous analyses have shown that if there were an influx of new STI cases into the MSM population, potentially imported from other areas or from bridging with heterosexual populations, reduced screening levels could lead to a rebound in infections [15].…”
Section: Discussionsupporting
confidence: 74%
“…These data sources do not separate symptoms-based testing and routine, asymptomatic screening. Model-calibrated values reflect a mixture of symptoms-based testing and asymptomatic screening, with the observed split similar to other empirical data, where <10% of testing events were symptoms-driven [22]. Reference models assumed only annual screening (0% HR coverage), given the lack of nationally representative data on screening frequency; a recent analysis suggested minimal associations of risk behavior and screening interval, where HIV-negative MSM screened, on average, less than annually [22].…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…Infrequent extragenital screening is a public health concern because of the higher prevalence of asymptomatic chlamydia or gonorrhea infections that may remain undetected [30]. Asymptomatic STIs at these sites also lead to increased risk of HIV infection among partners in the sexual network not using PrEP [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…ARTnet eligibility criteria included male sex at birth, current male identity, lifetime history of sexual activity with another man, and age between 15 and 65 years. The study, provided only in English, surveyed participants about recent sexual behaviors, HIV and STI screening, and egocentric network data [24]. We restricted the participants in this analysis to PrEP-eligible MSM, defined as MSM who had ever had an HIV test and who self-reported as HIV-negative.…”
Section: Methodsmentioning
confidence: 99%